Development of an ultra-small biomass gasification and power generation system: Part 1. A novel carbonization process and optimization of pelletization of carbonized wood char. (15th December 2017) - Ding, Lu; Yoshikawa, Kunio; Fukuhara, Minoru; Xin, Dai; Muhan, Li
Highlights: A novel carbonization and pelletization process of woody char was proposed. The carbonization process was almost an energy-free process. Poval was used as a binder for making pellets. An optimal ratio among char, water, and poval solution for making high-quality pellets. Abstract: Small-scale, distributed and low cost biomass power generation technologies are highly required in the modern society. The biomass pretreatment process, that is, a combination of carbonization and pelletization processes of cedar wood were explored in this study. For the carbonization process, a novel carbonizer composed of one carbonization chamber and one combustion chamber was tested, and the mass and energy balances during cedar wood carbonization at 400–500 °C were analyzed, respectively. During the initial heating stage, about 22 kg of wood with dry basis should be supplied into the combustion chamber through several batches. When the temperature in the carbonization chamber reached to the range of 200–220 °C, the combustion chamber could be self-heated by burning the pyrolysis gas (tar vapor, CH4, H2, CO) sent from the carbonization chamber. The specific wood consumption for producing 1 kg of wood char was within 3.6–4.4 kg, which presented an increase trend with increasing the carbonization temperature. Moreover, this carbonization system can deal with different kinds of biomass with various water contents and shapes. For the pelletization process, effects of adding amount of the binder (poval solution), water and the carbonization temperature on the pellet quality were studied so as to explore the optimal condition for making high quality pellets from the crushed wood char. The results indicated that there was an optimal ratio among char, added water, and the binder for making high quality pellets. Considering the energy transfer efficiency and pellet quality, the mass ratio of 0.93:0.32:0.10 for 450 °C-char in the dry basis: added water plus water in char: poval solution was the optimal condition for making high quality pellets.